Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

Improving soil quality and wheat yield via conservation tillage in a semiarid region: A long-term field study integrating microorganisms and ecoenzymatic stoichiometry - Linlin Wang; Lingling Li; Zhuzhu Luo; Junhong Xie (Soil and Tillage Research, 2026)

IGF1-IGF1R signaling in tumor-associated macrophages regulates extracellular matrix organization in BRAF inhibitor-targeted melanoma - Ya Luo; Linlin Liu; Xing Zhou; Jiao Yang; Min Tang; Wei Feng; Chunlan Du; Xiaobo Liu; Liu Yang; Fei Liu; Liqun Zhang (Molecular and Cellular Biochemistry, 2026)

Clinical and Molecular Characterization of Five Additional Individuals With SATB2-Associated Syndrome in Guangxi - Sheng Yi; Qinle Zhang; Fei Chen; Xunzhao Zhou; Qiang Zhang; Shang Yi; Xiaofei Zhang; Jiale Qian; Linlin Wang; Shujie Zhang; Biyan Chen; Zailong Qin; et al. (Biochemical Genetics, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

The ecological and economic impacts of national park pilot projects in China - Xiaobin Zhang; Heng Luo; Xianfan Shu; Linlin Zhang (Ecological Economics, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrogenation of heavy turpentine into high-energy-density biofuel over MOF-derived nano-Ni@C/rGO and associated kinetic insights - Xiaoying Tang; Yongxiong Yang; Ying Tang; Shen Luo; Xiaopeng Chen; Xu Wei; Linlin Wang (Journal of Environmental Chemical Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Study on the Separation of Co(II) Ions by Triethylenetetramine-Modified Polyacrylonitrile Nanofibers - Yang Luo; Shuyuan Liu; Weiwei Li; Guangchuan He; Guangfu Chen; Xianchen Huang; Xiangyang Niu; Jiahui Ruan; Linlin Huang; Guoyuan Yuan (Water, Air, & Soil Pollution, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Hominin occupation of the Western Qinling Mountains as early as ∼900 ka - Zaijun Li; Jian Wang; Chongwen Luo; Yongbo Quan; Linlin Yan; Yuanxin Li; Linxueyi Wang; Shengli Yang; Jia Jia; Ziwei Tao; Tingjiang Peng; Zhenzhong Tian; et al. (Science Bulletin, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Endophytic fungi-mediated drought tolerance in spring wheat under no-tillage with straw cover on the Loess Plateau, China - Changliang Du; Lingling Li; Junhong Xie; Khuram Shehzad Khan; Linlin Wang; Zhuzhu Luo; Lingzhi Li; Zechariah Effah; Muhammad Zahid Mumtaz (Soil and Tillage Research, 2026)

Influence of pore fluid on the elasto-plastic property of shales - Linghao Chen; Wanqing Shen; Shuitao Zhang; Zhilei Luo; Jianfu Shao; Linlin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

Drug screening reveals the mechanism of toyocamycin-induced apoptosis in triple-negative breast cancer organoids - Houshi Ma; Linlin Lu; Yuqing Tu; Xiaoran Chang; Huabin Jiang; Tianhang Yang; Shun Wang; Jinxian Wang; Jinbing Xue; Yan Chen; Gangyin Luo (Toxicology and Applied Pharmacology, 2026)

Bias-aware learning for unbiased scene graph generation in remote sensing imagery - Tingzhu Wang; Linlin Wang; Junwei Luo; Kang Wu; Yansheng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Atmospheric and room temperature plasma mutagenesis of Graesiella emersonii for enhanced protein production using methanol as novel carbon source - Jixu Luo; Guanqin Huang; Mingjia Zheng; Changqing Ou; Qingyue Chen; Yufeng Ling; Linlin Cai; Yang Yang; Lingcheng Liu; Fei Huang; Zhangli Hu; Yihong Zheng (Bioresource Technology, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Engineering efficient and stable CsPbBr3 perovskite nanocrystals via multi-functional molecular mediated surface strategy toward white light-emitting devices - Hanyun Yang; Haoqi Zhu; Linlin Ma; Mengwei Luo; Hang Guo; Lepeng Zhou; Wenxu Sun; Bin Xue; Lei Zhang (Chemical Engineering Journal, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

Birds of a Feather Self-Regulate Together: The Intersection of Peer Networks and Self-Regulated Learning in Biomedical Engineering - Linlin Luo; Joseph C. Tise; Megan S. Patterson; Daniel L. Alge; Paul R. Hernandez (Biomedical Engineering Education, 2025)

Zinc Deficiency Aggravates High-Fat Diet-Induced Renal Injury by Regulating Oxidative Stress and Inflammation via the Nrf2/HO-1 Pathway - Yucan Guan; Linlin Wu; Man Wu; Yuexin Zhu; Ping Luo; Manyu Luo (Biological Trace Element Research, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

The Use of Surrogate Matrix for Calibrators in the Analysis of Dried Blood Samples – A Feasibility Study - Dong Hun Lee; Iris Xie; Matthew Solomon; Ming Wang; Linlin Luo; Eric Woolf (The AAPS Journal, 2025)

Rational design of micro-cone array on copper host for dendrite-free sodium metal plating - Mengyang Xu; Chengwen Gao; Tsz Wing Tang; Linlin Zhang; Jiawen You; Xing Zhou; Mengjia Xu; Jang-Kyo Kim; Zhengtang Luo (Chemical Engineering Journal, 2025)

The impact of energy metabolic pattern on household carbon emissions: A spatio-temporal perspective in Guangdong-Hong Kong-Macao Greater Bay Area - Lei Chen; Jiahan Luo; Guotian Cai; Linlin Xia; Yongyang Wang; Linyu Xu (Sustainable Cities and Society, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

Finer topographic data improves distribution modeling of Picea crassifolia in the northern Qilian Mountains - Xiang Zhang; Linlin Gao; Yu Luo; Yiyun Yuan; Baolong Ma; Yang Deng (Journal of Mountain Science, 2024)

Study on China’s Farmland–Grain resource curse: Empirical testing based on 31 Provinces and 2843 Counties - Renyi Yang; Changbiao Zhong; Zisheng Yang; Shiqin Yang; Guanqiu Ji; Jingke Yu; Linlin Cao; Jinrong Yang; Lei Luo; Yicong Shen; Yongdong Zhang (Land Use Policy, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Copper-doped ZIF-67/wood aerogel for effective peroxymonosulfate activation - Linlin Zhao; Wanning Xiong; Ziheng Wang; Jie Ouyang; Mengyao Li; Gonggang Liu; Yongfeng Luo (Journal of Environmental Chemical Engineering, 2024)

An end-capping strategy for shape memory phthalonitrile resins via annealing enables conductivity and wave-absorption - Rongxiang Hu; Fenghua Zhang; Lan Luo; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Piezoelectric effect-assisted Z-scheme heterojunction ZnIn2S4/BaTiO3 for improved photocatalytic reduction of CO2 to CO - Shanyue Lu; Shengwei Zhang; Linlin Li; Cong Liu; Zhou Li; Dan Luo (Chemical Engineering Journal, 2024)

N-methyl pyrrolidone manufacturing wastewater as the electron donor for denitrification: From bench to pilot scale - Songyun Chen; Xiaohui Zhu; Ge Zhu; Bin Liang; Jin Luo; Danyang Zhu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Science of The Total Environment, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

Multidimensional cross-linked network strategies for Rapidly, Reconfigurable, refoldable shape memory polymer - Lan Luo; Fenghua Zhang; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

Electrochemical lithium ion pumps for lithium recovery: A systematic review and influencing factors analysis - Guiling Luo; Xiaowei Li; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Desalination, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Exploratory study on the potential regulating role of Peroxiredoxin 6 on proteolysis and relationships with desmin early postmortem - Xinyi Wang; Linlin Huang; Yimin Zhang; Lixian Zhu; Xiaoyin Yang; Huixin Zuo; Xin Luo; Yanwei Mao; David L. Hopkins (Meat Science, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Neutralization Activity of Anti-drug Antibodies Against a Biotherapeutic Can Be Predicted from a Comprehensive Pharmacokinetics, Pharmacodynamics, and Anti-drug Antibody Data Analysis - Weifeng Xu; Brian Maas; Brad Roadcap; Aparna Swarup; Thomas Steinmetz; Linlin Luo; Marina Ichetovkin; Sandra Wood; Faye Vazvaei-Smith; Andrew Wen-Tseng Lee; Kalpit Vora; Roy Helmy (The AAPS Journal, 2022)

When to Extend Monitoring of Anti-drug Antibodies for High-risk Biotherapeutics in Clinical Trials: an Opinion from the European Immunogenicity Platform - Gregor P. Lotz; Karin Benstein; Karien Bloem; Harm Buddiger; Claudio Calonder; Stefanie Elm; Elena Fernandez; Joanne Goodman; Boris Gorovits; Joanna Grudzinska-Goebel; Melody Janssen; Vibha Jawa; et al. (The AAPS Journal, 2022)
The determination of a tailored anti-drug antibody (ADA) testing strategy is based on the immunogenicity risk assessment to allow a correlation of ADAs with changes to pharmacokinetics, efficacy, and safety. The clinical impact of ADA formation refines the immunogenicity risk assessment and defines appropriate risk mitigation strategies. Health agencies request for high-risk biotherapeutics to extend ADA monitoring for patients that developed an ADA response to the drug until ADAs return to baseline levels. However, there is no common understanding in which cases an extension of ADA follow-up sampling beyond the end of study (EOS) defined in the clinical study protocol is required. Here, the Immunogenicity Strategy Working Group of the European Immunogenicity Platform (EIP) provides recommendations on requirements for an extension of ADA follow-up sampling in clinical studies where there is a high risk of serious consequences from ADAs. The importance of ADA evaluation during a treatment-free period is recognized but the decision whether to extend ADA monitoring at a predefined EOS should be based on evaluation of ADA data in the context of corresponding clinical signals. If the clinical data set shows that safety consequences are minor, mitigated, or resolved, further ADA monitoring may not be required despite potentially detectable ADAs above baseline. Extended ADA monitoring should be centered on individual patient benefit.

Variability of voriconazole concentrations in patients with hematopoietic stem cell transplantation and hematological malignancies: influence of loading dose, procalcitonin, and pregnane X receptor polymorphisms - Guangting Zeng; Linlin Wang; Lihong Shi; Huilan Li; Miaomiao Zhu; Jia Luo; Zanling Zhang (European Journal of Clinical Pharmacology, 2020)

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Characterizing the interactions of two lipid modifications with lipid rafts: farnesyl anchors vs. palmitoyl anchors - Tao Zhang; Qichao Luo; Linlin Yang; Hualiang Jiang; Huaiyu Yang (European Biophysics Journal, 2018)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Microarray gene expression analysis of Monochamus alternatus (Coleoptera: Cerambycidae) after treatment with a sublethal dose of chloramine phosphorus - Tong Lin; Linlin Luo; Chunmei Wei; Huajun Wu (Applied Entomology and Zoology, 2014)

Investigation and integrated molecular diagnosis of root-knot nematodes in Panax notoginseng root in the field - Linlin Dong; Hui Yao; Qiushi Li; Jingyuan Song; Ying Li; Hongmei Luo; Shilin Chen (European Journal of Plant Pathology, 2013)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Rhizobacteria (Pseudomonas sp. SB) assist phytoremediation of oily-sludge-contaminated soil by tall fescue (Testuca arundinacea L.) - Wuxing Liu; Jianying Sun; Linlin Ding; Yongming Luo; Mengfang Chen; Caixian Tang (Plant and Soil, 2013)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)